Woman as a motive for the formation of pre-Islamic prose text: A study in light of cultural patterns - Adnan, Sura; Idan, Ikhlas (Al-Adab Journal, 2024)
Women have formed a wide and great presence in society, they represent an important element and an integral part of social life, which is not complete without their presence, they are present at every time and place because they are the other side of life, they lived in a harsh natural environment with a volatile climate, and tribal life was based on invasion, plunder, and other things that happen in the lives of Arabs, yet she remained strong and steadfast and faced all the challenges that stood before her in order to prove herself, then she became a symbol of beautiful everything, and at the same time she was a symbol of suffering as well. In pre-Islamic life, women became the main axis around which circles revolved, women were a point of attraction, admiration, revelation, and inspiration, they bore most of the literary and prose works with their mark, they were the pole of the universe, the home of magic and beauty, and they were the ideal and most present model, as they took on an aesthetic model in all ages. Women have brought on these Arab traits that control the formation of man from his early childhood, so her influence on the movement of events was merely a reaction to the impact on her of everything that happened around her in her environment, in which she received blows one after the other as the tribes fought and made huge sacrifices of loss, orphan hood, deprivation and destitution in that era, and the woman was the victim every time, exhausting all her energies and contributions, and indeed all the energies and capabilities of society, and yet the Arab woman embodied all the great values that we see her in her creativity and her life. She has never abandoned these values that carry the reasons for life for her, and she has the greatest right and the greatest effort to create this life.